Effects of social facilitation and other factors on energy intake among students in a public university in Malaysia - Cheah, Khang Jin (2021)
While obesity levels have continued to rise, the factors thought to influence weight gain have broadened. In the past, how much people eat is often explained introduces into research literature, researchers have recognized environmental factor as part of the contributing factors for overweight and obese epidemic. The role of social influence as part of environmental factors may influence adoption of undesirable food intake and thus weight status. While obesity levels have continued to rise, the factors thought to influence weight gain have broadened. Recent studies have shown that the role of social influence as part of environmental factors may influence adoption of undesirable food intake and thus weight status. There is no published study on social influence under experimental study in Malaysia. Therefore, this study assessed the social influence specifically social facilitation effects along with other factors on energy intake in a laboratory setting. A within-subject experiment study design was utilized to investigate the social facilitation effects on energy intake. Multistage sampling method was used to select 64 subjects (50 female, 14 male) from a public university to participate in this study. After obtained the consent, a set of self-administered questionnaire on sociodemographic background, lifestyle factors (Global Physical Activity Questionnaire, GPAQ), trait anxiety (social interaction anxiety scale, SIAS), eating behavior (Eating Bevaior Questionnaire, EBQ) and nutrition knowledge (Nutrition Knowledge Survey) was distributed to the subjects. They were then invited to join three standardized lunch sessions under 3 social facilitation situations: ate alone (baseline), ate with unfamiliar peers, ate with familiar peers. The lunch sessions were scheduled at 1 week apart for 3 consecutive weeks. They were required to rate their anxiety level during eating rated 0 (calm) to 7 (very tense) each time after finished the lunch intake in the lab. A total of 64 university students (66% Malay, 34% Chinese) with a mean age of 23.6 years (SD=3.33 years) participated in this study. Majority of the subjects had normal BMI whereby the mean of BMI for male was 23.5 ± 6.74 kg/m2 and female was 21.1 ± 2.42 kg/m2. Repeated measures ANOVA revealed a statistically significant effect of social facilitation on energy intake with different social facilitation situations. On average, total energy intake at lunch was found to be increased when subjects ate with familiar peers (705 ± 170 kcal) compared to eating in a group with unfamiliar peers (587 ± 129 kcal) and eating alone (545 ± 119 kcal). Friedman test showed that there were significant differences in anxiety level (state anxiety) between three different social facilitation situations (p= 0.001). They felt most comfortable when eating with their familiar peers. Furthermore, adjusted generalized estimating equation (GEE) analysis showed only social interaction anxiety scale (p= 0.004) and anxiety during eating (p= 0.011) were associated with energy intake during meal time. energy intake, the impact is greater when eating in a group with familiar peers. Current findings also provide evidence that anxiety level during eating (state anxiety) could be the driver of social facilitation effects. It revealed that trait anxiety and state anxiety have dominant effects on energy intake during meal time compared to other influential factors such as body composition factors, physical activity level, nutrition knowledge level and eating behavior factor.